Mountain guides facing the effects of climate change. What perceptions and adaptation strategies at the foot of Mont Blanc? - Emmanuel Salim; Jacques Mourey; Ludovic Ravanel; Pietro Picco; Christophe Gauchon (Revue de Géographie Alpine)
The evolution of the high Alpine mountain environment, especially the cryosphere that faces climate change, deeply modifies the human activities that take place there. The mountaineering routes are directly impacted and they sometimes become inaccessible. In order to recover a good balance, adaptation is necessary. Mountain guides are among the most dependent professionals on the field on which they practice. As a result, they are probably the most impacted professionals but, at the same time, they are also those who can produce a lot of adaptation strategies. The aim of this paper is therefore to identify how mountain guides from Chamonix and Courmayeur are impacted and the different adaptation strategies they developed to face climate change. By this cross-border study, using quantitative and qualitative methods, this paper is also showing that the adaptation strategies are controlled by the territory dynamics.